Toward a Totalitarian Techno-Slave: Daft Punk’s Electroma - Hüseyin Serbes (Filmvisio)
The etymology of cyberpunk as a phenomenon that flourishes in the substrata of life is born from the notion of ‘cybernetics’ and the ethos of ‘punk’. Thus, it transforms the shock of the future into works of art that break away from the banality of everyday life. This study focuses on Electroma, a film with cyberpunk themes and motifs in which Thomas Bangalter and Guy-Manuel de HomemChristo, the iconic robot-members of the French electronic music formation Daft Punk, turn into directors and screenwriters. A sociological analysis is conducted of this film and the notion of robots. In this sense, it is aimed to analyze the work from the perspectives of ethics, esthetics and social movements. Throughout this study, in the context of cybernetic esthetics, the work’s narrative is explained within the framework of the concepts of entropy and redundancy in “Information Theory” proposed by Shannon. It has been observed that Electroma, which does not include any verbal dialog in its narrative, reflects a universe in which the real and the simulated are intertwined, as in other cyberpunk works based on high technology and robots.